Solidaritas dan Keadilan Sosial Menurut Gereja dalam Octogesima Adveniens - Maria Sonita Bay; Teresia Noiman Derung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to analyze the concepts of solidarity and social justice from the perspective of the Catholic Church as taught in the Octogesima Adveniens. The Church's social teachings, especially those related to solidarity and social justice, have an important role in encouraging the formation of a more just and humane society. This research uses a qualitative approach with a literature study method to analyze the main texts in Octogesima Adveniens as well as other relevant documents of the Church's social teachings. Content analysis was conducted to explore the concepts of solidarity and social justice contained in the encyclical, as well as its relation to the social, economic and political challenges of the time. The results show that the teachings in Octogesima Adveniens are still very relevant to be applied in dealing with the problem of social inequality in the modern world, with an emphasis on the importance of active participation of the faithful in changing unjust social structures. Solidarity and social justice, according to the Church, are not just a matter of theory, but also require real action to realize more just social change. The study concludes that the Church has an important role in guiding Catholics to realize a more inclusive and just society, and provides recommendations for the application of the principles of the Church's social teachings in today's socio-political context.